Impact of ionic doping on the normal and superconducting properties of YBCO thin films and nanowires - Balistreri, Angelo (My University, 2025)
Despite almost 40 years of intense research, high-temperature superconductivity in cuprates remains one of the most intriguing unsolved problems in condensed matter physics. The phase diagram of these materials, which describes how their properties vary with temperature and doping, is extremely complex: even the normal state above the superconducting critical temperature is characterized by multiple regions and symmetry-breaking orders associated with charge, magnetic, lattice, and orbital excitations. The interplay and competition among these orders, which may be at the origin of the pairing mechanism, are still far from being fully understood. In this thesis, to shed light on these phenomena and gain a clearer picture of normalstate orders and of their competition with superconductivity, we focus on YBa2Cu3O7−δ (YBCO), where doping is controlled by oxygen content, and we introduce a small fraction of Zn atoms substituting Cu. This chemical substitution modifies the CuO2 planes, which constitute the core of both the superconducting and normal-state properties of this family of materials. In particular, I optimized the growth of Zn-doped YBCO thin films on STO substrates via pulsed laser deposition. The partial substitution of Cu with non-magnetic Zn atoms effectively suppresses superconductivity, revealing the underlying normal-state properties hidden beneath the superconducting dome. To explore different regions of the phase diagram and understand the effect of Zn, films were grown across a range of oxygen dopings, from underdoped to strongly overdoped regimes, and for two different Zn concentrations. The structure, morphology, and transport properties of these films were characterized: these measurements allowed me to precisely determine the doping and build the complete phase diagrams for both Zn levels. Our results reveal a clear suppression of Tc, an expansion of the insulating region, and a relative invariance of the pseudogap temperature. Finally, the films were patterned into Hall bars and nanowires to investigate transport properties via currentvoltage characterization and transport measurements down to the nanoscale, providing information about material homogeneity at the nanodomain level. This work contributes to the broader effort of disentangling the mechanisms behind unconventional superconductivity by accessing the normal state through chemical doping. Moreover, it establishes a new material platform that paves the way for future investigations in both transport and spectroscopic experiments.
Keywords: YBCO Thin Films, Zn-doped, Phase diagram, Normal state, Nanowires